2022
DOI: 10.3389/fnagi.2022.790897
|View full text |Cite
|
Sign up to set email alerts
|

Self-Stigma in Parkinson's Disease: A 3-Year Prospective Cohort Study

Abstract: PurposeSelf-stigma is common in patients with Parkinson's disease (PD) and may lead to social isolation and delayed search for medical help. We conducted a 3-year prospective longitudinal study to investigate the development and evolution of self-stigma in patients with early stage PD and to explore the associated and predictive factors of self-stigma in PD.MethodA total of 224 patients with early stage PD (disease duration <3 years) were enrolled at baseline and followed up annually for 3 consecutive y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…There are studies that speak of rejection at work and stigmatization of patients diagnosed with a rare disease. Regarding the family environment, and coinciding with the studies of Lin et al [ 28 ], levels of dependence are observed that increase as the disease progresses. It is necessary to highlight the role of the main caregiver in the family environment, who should be taken into account as an essential character in the development of the disease, but should not be forgotten as an independent patient.…”
Section: Discussionsupporting
confidence: 83%
“…There are studies that speak of rejection at work and stigmatization of patients diagnosed with a rare disease. Regarding the family environment, and coinciding with the studies of Lin et al [ 28 ], levels of dependence are observed that increase as the disease progresses. It is necessary to highlight the role of the main caregiver in the family environment, who should be taken into account as an essential character in the development of the disease, but should not be forgotten as an independent patient.…”
Section: Discussionsupporting
confidence: 83%
“…Parkinson's disease (PD) is a chronic neurodegenerative disease marked by motor and non-motor symptoms, impacting both physical and mental well-being [1]. In addition to symptoms, people with PD often experience social isolation, stigma, and reduced self-esteem [2][3][4]. Current pharmacological or surgical interventions fall short of adequately treating these multiple facets of PD [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…These include components of the Parkinson’s Disease Questionnaire (PDQ-39) and Parkinson’s Disease Quality of Life Questionnaire (PDQL) [ 38 ]. For example, in China, Lin et al investigated the evolution of self-stigma in early-stage Parkinson’s (using PDQ-39), identifying a decrease in self-stigma with increasing disease progression [ 39 ]. The Stigma Impact Scale and Stigma Experience Scale have also been adapted to identify and measure perceived stigma in Parkinson’s (see Burgener and Berger [ 40 ]).…”
Section: Introductionmentioning
confidence: 99%